Defossilization and decarbonization of hydrogen production using plastic waste: temperature and feedstock effects during thermolysis stage - Veksha, Andrei (2023)
The replacement of natural gas with plastic-derived pyrolysis gas can defossilize H2 production, while subsequent capture, utilization and storage of carbon in a solid form can decarbonize the process. The objective of this study was to investigate H2 production from three types of plastics using a process comprising pyrolysis (600 °C) and thermolysis stages (1200-1500 °C). Depending on the plastic feedstock and thermolysis temperature, the laboratory-scale setup generated 1000-1350 mL/min product gas with H2 purity of 74.3-94.2 vol%. The recovery of 5-9 wt% molecular H2 per mass of plastics was achieved. Other products included solid residue (0.1-12 wt%) and oil (8-52 wt%) from the pyrolysis reactor, solid carbon (36-53 wt%) and gas impurities (2-16 wt%) from the thermolysis reactor. The purity of H2 gas was detrimentally influenced by polyethylene terephthalate in the feedstock due to the dilution of gas by CO. The decomposition of methane containing in the pyrolysis gas was the limiting reaction step during H2 production and improved at higher thermolysis temperature. Three solid carbon structures were formed during the thermolysis stage regardless of the plastic type: carbon black aggregates, carbon black aggregates coated with a layer of pyrolytic carbon and a carbon film on the inner reactor wall. Among the three types of carbon, the highest valorization potential was identified for carbon black aggregates. Plastic feedstock composition had little if any effect on carbon black properties, while high thermolysis temperature (1500 °C) reduced the particle sizes and increased the surface area of aggregates.